PENERAPAN MODEL QUANTUM TEACHING DENGAN MEDIA VISUAL DALAM PENINGKATAN PEMBELAJARAN IPS SISWA KELAS V SDN 2 KUTOSARI TAHUN AJARAN 2015/2016 - CAHYANINGTYAS, DWI (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Quantum Teaching Model Using Visual Media in Improving Social Science Learning for the Fifth Grade Students of SDN 2 Kutosari in the Academic Year of 2015/2016. The objectives of this collaborative Classroom Action Research (CAR) is to improve social science learning about Declaration of Indonesian Independence. Subjects of the research were the fifth grade students consisted of 13 boys and 13 girls. This research is conducted within three cycles. Techniques of collecting data were test, observation, and interview. The increase of students? learning mastery of social science learning from 3,85% to 84.62% in the first cycle, in the second cycle 90.39%, and in the third cycle 98.08%. Keywords: quantum teaching, visual media, social science learning Abstrak: Penerapan Model Quantum Teaching dengan Media Visual dalam Peningkatan Pembelajaran IPS Siswa Kelas V SDN 2 Kutosari. Penelitian tindakan kelas kolaboratif ini bertujuan untuk meningkatkan pembelajaran IPS tentang Proklamasi Kemerdekaan Indonesia. Subjek penelitian adalah siswa kelas V, terdiri dari 13 siswa laki-laki dan 13 siswa perempuan. Penelitian dilaksanakan dalam tiga siklus. Pengumpulan data menggunakan teknik tes, observasi, dan wawancara. Hasil penelitian menunjukkan ketuntasan pembelajaran siswa pada kondisi awal yaitu 3,85% meningkat menjadi 84,62% (siklus I), 90,39% (siklus II), dan 98,08% (siklus III). Kata Kunci: quantum teaching, media visual, pembelajaran IPS